Effects of an entomopathogenic fungus on the reproductive potential of Drosophila males. - Liao, A.; Cavigliasso, F.; Savary, L.; Kawecki, T.J. (Ecology and evolution, 2024)
While mortality is often the primary focus of pathogen virulence, non-lethal consequences, particularly for male reproductive fitness, are less understood; however, they are essential for understanding how sexual selection contributes to promoting resistance. We investigated how the fungal pathogen Metarhizium brunneum affects mating ability, fertility, and seminal fluid protein (SFP) expression of male Drosophila melanogaster paired with highly receptive virgin females in non-competitive settings. Depending on sex and dose, there was a 3-6-day incubation period after infection, followed by an abrupt onset of mortality. Meanwhile, the immune response was strongly induced already 38 h after infection and continued to increase as infection progressed. Latency to mate somewhat increased during the incubation period compared to sham-treated males, but even on Day 5 post infection >90% of infected males mated within 2 h. During the incubation period, M. brunneum infection reduced male reproductive potential (the number of offspring sired without mate limitation) by 11%, with no clear increase over time. Approaching the end of the incubation period, infected males had lower ability to convert number of mating opportunities into number of offspring. After repeated mating, infected males had lower SFP expression than sham controls, more so in males that mated with few mates 24 h earlier. Overall, despite strong activation of the immune response, males' mating ability and fertility remained surprisingly little affected by the fungal infection, even shortly before the onset of mortality. This suggests that the selection for resistance acts mainly through mortality, and the scope for fertility selection to enhance resistance in non-competing settings is rather limited.